EFFECTIVENESS OF CAREER PLANNING TRAINING TO HELP STUDENTS IN MAKING CAREER DECISIONS - Rizka Dara Vonna; Nur Hasmalawati (State Islamic University (UIN) Ar-Raniry, 2024)
Career decision making is a difficult process for high school students who are in adolescence. Generally, students experience obstacles in career selection due to lack of information about careers that make it difficult for students to make choices. The purpose of the research is to develop knowledge related to career planning that can help in student career decision making. Career planning training is given to help students make career decisions based on mature knowledge and understanding, rather than trusting career choices to the wishes of people around them. The research approach used a quasi-experimental method using a pretest and posttest design. This experimental design is used to measure before treatment is given and after treatment is given to the same group. The research subjects were 72 students of SMA Negeri 4 Banda Aceh. The results showed that career planning training had an influence on student career decision making with a value of 0.001 <0.05 (p<0.05), meaning that there were differences in career decision making after being given career planner training. This study successfully proved that the career planner training is effective in helping students in making career decisions after graduating from their current education. In conclusion, this training allows students to know what to do before deciding to choose a career and what to prepare to realize that career. Because so far, many students regret in the future due to choosing the wrong career.